34 Induction Therapy for Esthesioneuroblastoma (Controversies in Skull Base Surgery, 2019)
The impact of induction radiation and chemotherapy in the treatment of esthesioneuroblastoma has been inconclusive and unreliably reproduced, such that no definitive conclusions can yet be drawn regarding the potential benefits on survival and disease freedom. It is possible that the addition of induction therapy might prove beneficial to a subset of patients, yet it is unclear which patients stand to gain from such treatments and who might be harmed either from treatment complications, delayed or indefinitely postponed surgery, or incomplete resections. At this time, the cornerstone of esthesioneuroblastoma management remains an aggressive, clear-margin resection and adjuvant radiation therapy. Ultimately, a randomized trial is necessary, between patients who receive neoadjuvant therapy and those who undergo upfront surgical resection, controlling for Kadish stage and Hyams grade, while maintaining extensive resection, comparing morbidity, disease-free, and overall survival.
Keywords: chemotherapy; esthesioneuroblastoma; induction therapy; neoadjuvant; radiation